Dapagliflozin mitigates ovalbumin-prompted airway inflammatory-oxidative successions and associated bronchospasm in a rat model of allergic asthma. (4th May 2022) - Tabaa, Manar Mohammed El; Fattah, Aliaa Mohammed Kamel; Shaalan, Mohamed; Rashad, Eman; El Mahdy, Nageh Ahmed
ABSTRACT: Background: Asthma is a chronic inflammatory lung disease that universally affects millions of people. Despite numerous well-defined medications, asthma is poorly managed. This study aims to clarify the potential therapeutic effect of Dapagliflozin (DAPA) against lung inflammation, oxidative stress, and associated bronchospasm in OVA-sensitized rat asthma model. Research design and methods: Twenty-five rats were allocated into (Control, Asthma, DEXA, DAPA, and DAPA+DEXA). All treatments were administered orally once a day for two weeks. The BALF levels of IL-17, TNFα, IL-1β, and MCP-1 were determined to assess airway inflammation. For oxidative stress determination, BALF MDA levels and TAC were measured. The BALF S100A4 level and NO/sGC/cGMP pathway were detected. Lung histopathological findings and immunohistochemical investigation of eNOS and iNOS activities were recorded. Results: DAPA significantly reduced (p < 0.001 ) airway inflammatory-oxidative markers (IL-17, TNFα, IL-1β, MCP1, and MDA), but increased (p < 0.001 ) TAC, and mitigated bronchospasm by activating NO/sGC/cGMP and reducing S100A4 (p < 0.001 ). The biochemical and western blot studies were supported by histopathological and immunohistochemical investigations. Conclusions: DAPA presents a new prospective possibility for future asthma therapy due to its anti-inflammatory, anti-oxidant, and bronchodilator properties. DAPA has the property of reducing Dexamethasone (DEXA)-associated unfavorable effects during asthma treatment.